Dielectric Relaxation Studies of Hydrogen Bonded Complexes of Benzamide and Acetamide with Halogenated Phenols Using X-band Microwave Frequency - A. Aathif Basha; F. Liakath Ali Khan (ASEAN Journal on Science and Technology for Development, 2021)
At 308 K, using a 9.37 GHz dielectric relaxation setup, dielectric studies of hydrogen bonded complexes of benzamide and acetamide with 4-fluorophenol, 4-bromophenol, 4-chlorophenol, and 4-iodophenol in benzene were performed. Various dielectric parameters (such as ?', ?'', ?0, ??) were tested. The steric interactions of the proton donor determined the group rotation relaxation time t(2), whereas the significance of the single frequency method of Higasi et al. for multiple relaxation time t(1) was determined by the hydrogen bonding power of the phenolic hydrogen. The presence of a 1:1 complex system between the prepared samples, as well as a charge transfer between the free hydroxyl group of phenols and the carbonyl group of amides was confirmed by the fact that the relaxation time and molar free energy activation of the 1:1 molar ratio were greater than some other higher molar ratios (i.e. 3:1, 2:1, 1:2, 1:3).